Towards a Team Approach to Understanding Board Effectiveness - Wildenauer , Michael (Journal of Law and Governance, 2015)
Research into board effectiveness has often been approached from a structural perspective and investigated using the financial performance of the organization, with limited success. However, boards are also elite teams and their effectiveness can this be studied in terms of group constructs. This paper provides a review of the literature which exists to support a team effectiveness approach to the effectiveness of boards, and exactly which parts of the team effectiveness literature are most suitable for behavioural research into board effectiveness.